Using Word Wall Media In Improving Student’s Mastery In Reading - Simanjuntak, Marini; Widyantoro, Agus (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to determine the Utilization of Word Wall Media in Improving Reading Mastery of Class X TAB Students at SMK Negeri 3 Tanjung Selor. This research is a type of class action research. Sampling techniques are observation, interview, questionnaire and documentation. Data analysis is quantitative analysis with an experimental approach. The results showed that the pretest scores ranged from 40 to 75 with an average score of 60.97. Meanwhile, posttest scores range from 70 to 100. Thus, it can be concluded that vocabulary mastery increases significantly after using Word Wall Media and the analysis results of this research show a significant difference in students' vocabulary proficiency in reading descriptive texts when taught using word wall media compared to when taught without media in class X at SMK Negeri 3 Tanjung Selor. This can be seen from the obtained data, The t-value of -30.68 with a p-value (Sig. 2-tailed) of 0.000 shows that the difference between the pretest and post-test scores is statistically significant. Since the p-value is less than 0.05, we can conclude that the improvement in vocabulary is not due to chance.